2012
DOI: 10.1371/journal.pgen.1002721
|View full text |Cite
|
Sign up to set email alerts
|

UDP-Galactose 4′-Epimerase Activities toward UDP-Gal and UDP-GalNAc Play Different Roles in the Development of Drosophila melanogaster

Abstract: In both humans and Drosophila melanogaster, UDP-galactose 4′-epimerase (GALE) catalyzes two distinct reactions, interconverting UDP-galactose (UDP-gal) and UDP-glucose (UDP-glc) in the final step of the Leloir pathway of galactose metabolism, and also interconverting UDP-N-acetylgalactosamine (UDP-galNAc) and UDP-N-acetylglucosamine (UDP-glcNAc). All four of these UDP-sugars serve as vital substrates for glycosylation in metazoans. Partial loss of GALE in humans results in the spectrum disorder epimerase defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 18 publications
1
35
0
Order By: Relevance
“…11 It has also been found that UDP-galactose 4-epimerase plays an essential role in development and homeostasis of Drosophila that extends beyond the Leloir pathway. 12 On the other hand, UDP-sugars are also important as precursors in lipopolysaccharides (LPS). LPS is involved in several aspects of cell-cell interactions, such as host-pathogen interactions 13 and biofilm formation.…”
Section: General Introductionmentioning
confidence: 99%
“…11 It has also been found that UDP-galactose 4-epimerase plays an essential role in development and homeostasis of Drosophila that extends beyond the Leloir pathway. 12 On the other hand, UDP-sugars are also important as precursors in lipopolysaccharides (LPS). LPS is involved in several aspects of cell-cell interactions, such as host-pathogen interactions 13 and biofilm formation.…”
Section: General Introductionmentioning
confidence: 99%
“…In contrast, more abundant intracellular UDP-glucose coincided with higher galactosylation. The enzyme UDP-galactose 4'-epimerase interconverts UDP-glucose and UDP-galactose in the final step of the Leloir pathway of galactose metabolism, while galactose-1-phosphate uridyl transferase is involved in the second step of the pathway, catalyzing the transformation of UDP-glucose and galactose-1-phosphate to glucose-1-phosphate and UDP-galactose 124,302 . In comparison to other process formats, in process A the substrate demand of galactosyltransferase was lower after day 6.…”
Section: Discussionmentioning
confidence: 99%
“…al. [32], Daenzer and colleagues [7] created a time course series of Drosophila that experienced dGALE knockdown with concurrent induction of either hGALE, eGALE, wbgU , or both eGALE and wbgU at successive stages of development. As expected, RNAi knockdown of dGALE during both embryonic and larval stages of development was lethal, but was rescued by expression of either hGALE or eGALE + wbgU .…”
Section: A D Melanogaster Model Of Epimerase Deficiency Galactosemiamentioning
confidence: 99%